IgG4-Related Disease without Overexpression of IgG4: Pathogenesis Implications - Naoshi Nishina; Yuko Kaneko; Masataka Kuwana; Hironari Hanaoka; Hideto Kameda; Shuji Mikami; Tsutomu Takeuchi (Case Reports in Rheumatology)
IgG4-related disease is a new disease group that affects multiple organs. It is characterized by high serum IgG4 and abundant infiltration of IgG4-bearing plasma cells in the affected organ. Here, we describe an intriguing case that suggested that IgG4-related disease might present without IgG4 overexpression or infiltration, at least during a relapse. A 47-year-old man had been diagnosed with systemic lupus erythematosus 15 years. He was admitted due to a pituitary mass, systemic lymphadenopathy, and multiple nodules in the lungs and kidneys. The serum IgG4 level was normal and histopathological examination of the pituitary mass showed abundant lymphocyte and plasma cell infiltration with very few IgG4-positive cells. When we examined specimens preserved from 15 years ago, we found high serum IgG4 levels and IgG4-bearing plasma cell infiltration. This resulted in a diagnosis of IgG4-related disease, and we considered the current episode to be a relapse without IgG4 overexpression. This case indicated that, to clarify the pathogenesis of IgG4-related disease, current cases should repeat specimen evaluations over the course of IgG4-related disease to define diagnostic markers.